KAJIAN MENGENAI PERCERAIAN MENURUT PEMIKIRAN RAJA ALI HAJI: REFLEKSI SYAIR SULUH PEGAWAI - Sibarani, Citra Dewi; Buduroh, Mamlahatun (Universitas Lancang Kuning, 2024)
The manuscript of Syair Suluh Pegawai is a literary work authored by Raja Ali Haji, addressing aspects of marital life, including divorce. This syair serves as a guide for officials involved in marital affairs. In addition to outlining marriage guidelines and regulations, Raja Ali Haji also incorporates verses concerning divorce cases, notably through the narrative